STUDY ON SOIL QUALITY CHARACTERISTICS AND SPATIAL DIFFERENCE OF THE WALNUT PRODUCING AREA IN HUBEI PROVINCE OF CHINA - M. Li; Y. J. Xu; H. Wang; L. Y. Yuan; X. R. Wang; J. Z. Li; D. J. Zhang; F. X. Huang (Journal of Animal and Plant Sciences, 2022)
To study the soil pH value, quality characteristics of organic matter, and available elements in intensive cultivation of walnut orchards in different areas of Hubei Province, and to provide the scientific basis for the soil management of walnut orchards in different areas，the distribution frequency and correlation of the pH value, organic matter and alkalescence N, availableP, availableK, availableCa, availableMg, availableS,availableFe, availableZn, andavailableB in 135 walnut orchards from 6 walnut production areas in Hubei Province were analyzed by a typical sampling method. The differences and main sources of comprehensive fertility coefficients in different production areas were also analyzed. The distribution frequency of organic matter and available elements in walnut orchards were unbalanced. Available P was the most skewed with 55.67%. The soil organic matter content was significantly correlated withthe contents of alkalescence N, available P, available K, available Mg, available Fe, available Zn and available B. The comprehensive soil fertility coefficient ranged from 1.21 to 1.84, with an average of 1.52, which was the general fertility level. The maximum limiting factor of soil fertility was available S, followed by alkalescence N and available P. There were significant differences in comprehensive soil fertility among different walnut production areas. 92.67% of the differences came from within the production areas, and 7.33% from between production areas. The highest differentiation coefficients were available K and available P, which were 26.20% and 10.79%, respectively. The contents of alkalescence N and P were elements that affect the soil fertility of walnut production areas in Hubei Province. And the skew amounts and differentiation coefficients of P were larger than other elements. In view of the significant positive correlation between organic matter content and most soil elements, in order to improve the comprehensive soil fertility, it is suggested that soil management should focus on increasing soil organic matter, the application of phosphorus fertilizer and improving the availability of phosphorus.
Keywords: Walnut; Soil; Comprehensive fertility coefficient; Spatial difference